A theoretical study on the stability of the classical phases of surfactant-water systems in the temperature-concentration phase diagram. Issue 1 (12th December 2021) - Gupta, Santosh Prasad; Kaushal, Avinash Kant; Gaurav, Nishant Ketu; Kumari, Sunita; Kumari, Sadhana; Kumar, Purushottam
Abstract: In the present study, we have used a mean field theory that is also a modified Ginzburg-Landau expansion in the order parameter. Single mode expansion of the order parameter were taken and written in terms of the reciprocal lattice vectors corresponding to the first reflection of the classical phases in such a way that the corresponding contour plot exhibits the required features of the respective phases. 'Wolfram Mathematica 8.0' software was used for calculations and the free energy optimizations. The present theory stabilizes the classical phases in the concentration – temperature phase diagram. And percentage of the stabilized area for the lamellar, hexagonal, and BCC phases, are found to be 35.41%, 42.98%, and 21.61%, respectively.